Patient characteristics and acute cardiovascular event rates among patients with very high‐risk and non‐very high‐risk atherosclerotic cardiovascular disease. Issue 10 (5th August 2021) - Fonarow, Gregg C.; Kosiborod, Mikhail N.; Rane, Pallavi B.; Nunna, Sasikiran; Villa, Guillermo; Habib, Mohdhar; Arellano, Jorge; Mues, Katherine E.; Sun, Kainan; Wade, Rolin L.
Abstract: Background: The risk for subsequent major cardiovascular (CV) events among patients with very high‐risk (VHR) atherosclerotic CV disease (ASCVD) remains to be fully elucidated. Hypothesis: We assessed the characteristics and major CV event rates of patients with VHR versus non‐VHR ASCVD in a real‐world setting in the United States (US), hypothesizing that patients with VHR ASCVD would have higher CV event rates. Methods: This was a retrospective cohort study conducted from January 01, 2011, to June 30, 2018, in the US using the Prognos LDL‐C database linked to the IQVIA PharMetrics Plus® database supplemented with the IQVIA prescription claims (Dx/LRx) databases. Patients were ≥18 years old and had ≥2 non‐ancillary medical claims in the linked databases at least 30 days apart. The study was conducted in 2 stages: (1) identification of patients with ASCVD who met the definition of VHR ASCVD and a matched cohort of non‐VHR ASCVD patients using the incidence density sampling (IDS) approach; (2) estimation of the occurrence of major CV events. Results: Among patients with ≥1 major ASCVD event ( N =147, 679), most qualified as VHR ASCVD (79.5%). There were 115, 460 patients each in IDS‐matched VHR and non‐VHR ASCVD cohorts. The composite myocardial infarction/ischemic stroke event rates in the VHR and non‐VHR ASCVD cohorts were 8.04 (95% confidence interval [95% CI]: 7.87‐8.22) and 0.82 (95% CI: 0.77‐0.88) events per 100 patient‐years, respectively, during the 1‐year post‐index period. Conclusions: Most patients with ≥1 previous major ASCVD event treated in real‐world US clinical practice qualified as VHR ASCVD. Patients with VHR ASCVD had much higher rates of major CV events versus non‐VHR ASCVD patients.